Restarting elective orthopaedic services during the COVID-19 pandemic: Do patients want to have surgery? - Chang, Justin (Bone Jt Open, 2020)
AIMS: As the peak of the COVID-19 pandemic passes, the challenge shifts to safe resumption of routine medical services, including elective orthopaedic surgery. Protocols including pre-operative self-isolation, COVID-19 testing, and surgery at a non-COVID-19 site have been developed to minimize risk of transmission. Despite this, it is likely that many patients will want to delay surgery for fear of contracting COVID-19. The aim of this study is to identify the number of patients who still want to proceed with planned elective orthopaedic surgery in this current environment. METHODS: This is a prospective, single surgeon study of 102 patients who were on the waiting list for an elective hip or knee procedure during the COVID-19 pandemic. Baseline characteristics including age, ASA grade, COVID-19 risk, procedure type, surgical priority, and admission type were recorded. The primary outcome was patient consent to continue with planned surgical care after resumption of elective orthopaedic services. Subgroup analysis was also performed to determine if any specific patient factors influenced the decision to proceed with surgery. RESULTS: Overall, 58 patients (56.8%) wanted to continue with planned surgical care at the earliest possibility. Patients classified as ASA I and ASA II were more likely to agree to surgery (60.5% and 60.0%, respectively) compared to ASA III and ASA IV patients (44.4% and 0.0%, respectively) (p = 0.01). In addition, patients undergoing soft tissue knee surgery were more likely to consent to surgery (90.0%) compared to patients undergoing primary hip arthroplasty (68.6%), primary knee arthroplasty (48.7%), revision hip or knee arthroplasty (0.0%), or hip and knee injections (43.8%) (p = 0.03). CONCLUSION: Restarting elective orthopaedic services during the COVID-19 pandemic remains a significant challenge. Given the uncertain environment, it is unsurprising that only 56% of patients were prepared to continue with their planned surgical care upon resumption of elective services. Cite this article: Bone Joint Open 2020;1-6:267–271.